Dari Jawa menuju Atjeh : kumpulan tulisan tentang politik, Islam, dan gay - Christanty, Linda, 1970- (Jakarta : Kepustakaan Populer Gramedia, 2009)
Issue on condition of social and politics in Indonesia; collected of articles.
Keywords: Indonesia -- Social conditions; Indonesia -- Politics and government